A LITERATURE REVIEW ON ISLAMIC CONTRACTS IN SHARIA FINANCING - Mabrur, Imam; Andani, Merry; Jaiti, Nur; Nur'aini, Nur'aini (UIN Sumatera Utara, 2025)
This study aims to identify, classify, and analyze various Islamic financing contracts, including traditional types and contemporary multi-contract structures, in response to evolving economic and financial technologies. Employing a Systematic Literature Review (SLR) and qualitative-descriptive method, the study examines literature from 2015 to 2025 sourced from major academic databases. Findings indicate that murabahah, ijarah, musyarakah, and mudharabah remain core instruments, while hybrid models such as IMBT and murabahah-wakalah are increasingly adopted to address complex financing needs. Supporting contracts, such as wakalah, kafalah, rahn, hiwalah, qardh, and wadiah, play a strategic role in ensuring legal compliance, operational efficiency, and financial inclusion. The study highlights the urgency of contract systematization to enhance the effectiveness, Sharia compliance, and innovation of Indonesia’s Islamic finance system.Keywords: Islamic contracts; Islamic financing; contract classification; Shariah-compliant finance; Islamic financial instruments